Prevalence of Scabies in Skin and VD OPD of Faridpur Medical College Hospital (Faridpur Medical College Journal, 2016)
The burden of scabies is highest in tropical countries, but recent data from Bangladesh is scanty. This cross sectional study was carried out to find the prevalence of scabies in skin & VD Out Patient Department (OPD) of Faridpur Medical College Hospital (FMCH) during the period of April 2013 to March 2014. Total 22,399 patients attended to the skin & VD OPD, were included in this study. We identified 15,455 patents with scabies. The total prevalence was 69%. Prevalence in January was highest & was 78%. Most cases were uncomplicated but 17.28% of complicated scabies patients were found. Scabies was more in poor socio-economic group than others. The present study showed a high prevalence of scabies in patients presenting to skin & VD OPD, FMCH. Prevalence was higher overall in children. Our data show that scabies is common in patients presenting to skin & VD OPD & this finding may be used as an indicator of the general population.Faridpur Med. Coll. J. Jan 2015;10(1): 17-19